Assessment on the present status of coastal fisheries at Gurunagar, Jaffna - Thivviyan, S.; Jayakody, D.S. (Faculty of Science, University of Jaffna, 2015)
Fishery is a major income source of the Sri Lankan people resides in the coastal region. Among those, Jaffna contributes a considerable proportion to the total fishery production of the island which was 4.5% of the total fish production in Sri Lanka in 2013. This study aimed to collect recent updated fisheries information as the government already identified Gurunagar as a potential site in Jaffna to develop to the status of a harbor. Fishery related data was collected during the period April to June 2015 from commercial fishing vessels and sirakuvalai fishing operations landed at Gurunagar. Primary data was collected through direct observations during the field visits and secondary information was collected from the records of the Fisheries office at Jaffna. Catch, effort species composition, fishing craft and gear information were collected from randomly selected fishing crafts on randomly selected days. Fishers at Gurunagar engage in different fishing practices. Fishing activities of this area are regulated by the Fisher’s societies with the assistance of Department of Fisheries and Aquatic Resources. A total number of 28 species, representing 22 families were identified in commercial landings during the study period and also the species diversity and size of the fish (2.4 cm - 69 cm) varied with gear types. The types of gears used varied with the craft types. The catch rates of Outboard Fiber Reinforced Plastic Boats (OFRP - one day boats) recorded as higher than in-board day boats. Total fish production was recorded as around 128 tons during the study period. Production of sirakuvalai was accounted for 7.4 % of the total production in the study area. Commercial production per day is recorded around 3972.5 kg/Day and the average number of boats actively operated is 150. The existing facilities in the Gurunagar landing site for anchoring boats, sorting the catches, auctioning, storing and distribution are not up to the level required for an export oriented fish landings. Results of the present study suggest the need of further monitoring of this landing site to gather reliable information at least one year of time to cover seasonal variations of fish landings.